Invitation strategies and coverage in the population-based cancer screening programmes in the European Union. Issue 2 (March 2019) - Vale, Diama B.; Anttila, Ahti; Ponti, Antonio; Senore, Carlo; Sankaranaryanan, Rengaswamy; Ronco, Guglielmo; Segnan, Nereo; Tomatis, Mariano; Žakelj, Maja P.; Elfström, Klara M.; Lönnberg, Stefan; Dillner, Joakim; et al.
Abstract : The aim of this study was to describe the compliance of the population-based cancer screening programmes in the European Union Member States to the invitation strategies enumerated in the European Guidelines and the impact of such strategies on the invitational coverage. Experts in screening programme monitoring from the respective countries provided data. Coverage by invitation was calculated as the proportion of individuals in the target age range receiving a screening invitation over the total number of annualized eligible population. The invitation strategies of 30 breasts, 25 cervical and 27 colorectal national or regional population-based screening programmes are described. Individual mail invitations are sent by 28 breasts, 20 cervical and 25 colorectal screening programmes. Faecal occult blood test kits are sent by post in 17 of the colorectal cancer screening programmes. The majority of programmes claimed to have a population registry, although some use health insurance data as the database for sending invitations. At least 95% invitation coverage was reached by 16 breast, six cervical and five colorectal screening programmes. Majority of the programmes comply with the invitation strategies enumerated in the European guidelines, although there is still scope for improvements. Coverage by invitation is below the desirable level in many population-based cancer screening programmes in European Union.